Assessing the effect of omega-3 fatty acid combined with vitamin D3 versus vitamin D3 alone on estradiol levels: a randomized, placebo-controlled trial in females with vitamin D deficiency - Al-Shaer AH (Dove Medical Press, 2019)
Amani H Al-Shaer,1 Mahmoud S Abu-Samak,1 Luai Z Hasoun,1 Beisan A Mohammad,1,2 Iman A Basheti1 1Department of Clinical Pharmacy and Therapeutics, Applied Science Private University, Amman, Jordan; 2Department of Physiological Sciences, Fakeeh College for Medical Sciences, Jeddah, Kingdom of Saudi Arabia Purpose: Outcomes investigating the effect of vitamin D3 (VD3) and omega-3 fatty acids (Omega-3FA) on serum estradiol (E2) are scarce and conflicting. No previous study has investigated the effect of VD3 combination with Omega-3FA on E2 levels. This study was designed to investigate the effect of VD3, Omega-3FA and VD3 plus Omega-3FA on serum E2 levels in premenopausal females diagnosed with vitamin D deficiency (VDD).Subjects and methods: This randomized, placebo-controlled clinical trial was designed to evaluate the effects of 50,000 IU VD3 taken weekly, 300 mg Omega-3FA taken daily and their combination by the study participants for 8 weeks. The mid-follicular serum levels of E2 and 25-hydroxy vitamin D (25OHD) were assessed at 8 weeks. The study was conducted during winter on a convenience sample of healthy premenopausal Jordanian females with diagnosed VDD. Fasting serum levels for 25OHD and E2 were assessed at baseline and the end of the trial (after 8 weeks). Data were entered into SPSS and analyzed.Results: Healthy premenopausal Jordanian females (N=86) with diagnosed VDD, mean age 32.8±8.9 years, were recruited into the study. Supplementation of VD3 alone resulted in a significant increase in serum 25OHD (13.4±7.9–28.2±7.1 ng/mL, P<0.001) and a significant decrease in E2 levels (85.7±16.5–60.3±20.6 pg/mL, P=0.001). Omega-3FA intake led to a significant decrease in serum 25OHD levels (21.2±12.8–13.6±9.2 ng/mL, P=0.001) and a significant increase in E2 levels (56.3±19.2–78.4±23.7 pg/mL, P=0.006). Combination therapy (VD3 plus Omega-3FA) resulted in a significant increase in both 25OHD (12.0±4.7–35.1±9.5 ng/mL, P<0.001) and E2 (43.0±23.4–57.3±31.5 pg/mL, P=0.028) levels.Conclusion: Results of this study provide vital insight into the effects of D3, Omega-3FA and a combination of their supplementation on premenopausal Jordanian females with diagnosed VDD. Eight weeks of therapy led to decreased E2 level by VD3 and increased level by Omega-3FA supplementation. With regard to 25OHD, its level was increased by VD3 and decreased by Omega-3FA supplementation. Combination of VD3 plus Omega-3FA increased the levels of both E2 and 25OHD.Trial registration: This trial was registered at clinicaltrials.gov as NCT03333564. Keywords: vitamin D3, omega-3 fatty acids, serum levels of estradiol, premenopausal females, vitamin D deficiency, cancer